Grain dust explosions up in 1993 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Reversing a twelve year downward trend, there were 13 grain dust explosions reported for the U.S. in 1993 according to Robert W. Schoeff, Consultant and Professor Emeritus, Kansas State University and Ralph Regan, Safety Director, USDA-FGIS. This compares to a record low of 6 in 1992 and a ten-year average of 15 explosions.
Keywords: Grain dust; Dust explosions